The Transformation of Puppet Show in Central Thailand to Northeastern Part : A Case Study of the Rodsirinilsil and Petchnongrue Troupes. - ภูยาทิพย์, ภัทรนันท์; มณีวัฒนา, ชุติมา (Journal of Fine and Applied Arts Khon Kaen University, 2019)
The purpose of this research is to transform the puppet show of central region to the north - eastern region show. This research used qualitative research methodology by case study of Rodsirinilsil Troupes and Petchnongrue Troupes from study text, documents and relative research. The collecting field data was done by interviewing puppet show experts so as to analyze data and conclude the result of research. The results are as follows: 1) Plots of Petchnongrue troupe are mainly adapted from Northeastern folklores and “Lakorn Nai”. Also, the troupe adds some jokes to the stories. 2) Petchnongrue troupe make their puppets by using accessible materials such as plastic pipes. 3) Petchnongrue troupe adapt its costumes from costumes used in a Central Thai puppet show; however, the troupe make them more casual according to a simple way of life of people in the Northeastern region of Thailand. 4) Some western musical instruments are played in the shows. 5) Some gadgets in everyday life - Cell phones - are used in a show of Petchnongrue troupe. 6) Petchnongrue troupe design their stage in a simple structure. The stage is relatively similar to a ‘Mor Lum’ stage. The scene is made of Vinyl sheet. 7)The movement of the puppets in a show of Petchnongrue troupe is more similar to human movement. In conclusion, the changes of characteristics of Central Thai Puppetry in the puppets and the shows of Petchnongrue troupe signifies the transformation from Court Arts into Folk Arts. The puppets and the shows are adapted to Northeastern Thai style. The puppets of the troupe can be considered to be Applied Arts as there are changes and creativity in the shows and the puppets. The shows of Petchnongrue troupe also reflect the simplicity, fun-loving, and the cultural openness of people in the Northeast of Thailand.